2022
DOI: 10.1332/239788221x16308602886127
|View full text |Cite
|
Sign up to set email alerts
|

Under reconstruction: the impact of COVID-19 policies on the lives and support networks of older people living alone

Abstract: In the spring of 2020, the Austrian government introduced COVID-19 containment policies that had various impacts on older people living alone and their care arrangements. Seven qualitative telephone interviews with older people living alone were conducted to explore how they were affected by these policies. The findings show that the management of everyday life and support was challenging for older people living alone, even though they did not perceive the pandemic as a threat. To better address the needs of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Bundy et al (2021) investigated loneliness from already lonely older adults and found that many participants did not attribute the loneliness to the pandemic: "It's not been a whole lot, because I was already sitting around the house a whole lot anyway (…). It's basically the same, pretty well … I'd pretty well be like this anyway with COVID or without COVID" (p. 873) (see also Pfabigan et al, 2022).…”
Section: Theme 4 Impact On Well-beingmentioning
confidence: 97%
See 4 more Smart Citations
“…Bundy et al (2021) investigated loneliness from already lonely older adults and found that many participants did not attribute the loneliness to the pandemic: "It's not been a whole lot, because I was already sitting around the house a whole lot anyway (…). It's basically the same, pretty well … I'd pretty well be like this anyway with COVID or without COVID" (p. 873) (see also Pfabigan et al, 2022).…”
Section: Theme 4 Impact On Well-beingmentioning
confidence: 97%
“…Social connectivity and support from family and community were found in fourteen of the studies as important themes (Akkus et al, 2021;Chemen & Gopalla, 2021;Derrer-Merk et al, 2022b;Falvo et al, 2021;Fiocco et al, 2021;Greenwood-Hickman et al, 2021;Hafford-Letchfield et al, 2022;Huntley & Bratt, 2022;Jiménez-Etxebarria et al, 2021;Kremers et al, 2022;Kulmala et al, 202 1;Pfabigan et al, 2022;Prigent et al, 2022;Yang et al, 2021).…”
Section: Theme 3 Social Connectivitymentioning
confidence: 99%
See 3 more Smart Citations